Differences of connectivity between ESRD patients with PD and HD. Issue 8 (24th June 2020) - Park, Bong Soo; Seong, Myungjun; Ko, Junghae; Park, Si Hyung; Kim, Yang Wook; Hwan Kim, Il; Park, Jin Han; Lee, Yoo Jin; Park, Seongho; Park, Kang Min
Abstract: Objectives: The aim of this study was to investigate alterations in structural and functional brain connectivity between patients with end‐stage renal disease (ESRD) who were undergoing peritoneal dialysis (PD) and hemodialysis (HD). Methods: We enrolled 40 patients with ESRD who were undergoing PD (20 patients) and HD (20 patients). We also enrolled healthy participants as a control group. All of the subjects underwent diffusion tensor imaging (DTI) and resting‐state functional magnetic resonance imaging (rs‐fMRI). Using data from the structural and functional connectivity matrix based on DTI and rs‐fMRI, we calculated several network measures using graph theoretical analysis. Results: The measures of global structural connectivity were significantly different between the patients with ESRD who were undergoing PD and healthy subjects. The global efficiency and local efficiency in the patients with PD were significantly decreased compared with those in healthy participants. However, all of the measures of global structural connectivity in the patients with HD were not different from those in healthy participants. Conversely, in the global functional connectivity, the characteristic path length was significantly increased and the small‐worldness index was decreased in patients with HD. However, the measures of the global functional connectivity in the patients with PD were not different from those in healthy subjects. Conclusion: This study revealed that alterations in structural and functional connectivity in patients who were undergoing PD and HD were different than those in healthy controls. These findings suggest that brain networks may be affected by different types of renal replacement therapy. Abstract : Alterations in structural and functional connectivity in ESRD patients who were undergoing PD and HD were different than those in healthy controls. The measures of global structural connectivity were significantly different between the patients with ESRD who were undergoing PD and healthy subjects. In the global functional connectivity, the network measures in patients with HD were different from those of the healthy controls.